Health Promoting Lifestyle and its Relationship with Self-Efficacy in Iranian Mastectomized Women - Hamed Bieyabanie, Monireh (Asian Pac J Cancer Prev, 2020)
INTRODUCTION: Lifestyle modification has an important role in long-term health of breast cancer patients. As a result, this study aimed to identify the health-promoting lifestyle and its subdomains in mastectomized women and its relationship with self-efficacy. MATERIALS AND METHODS: This cross-sectional study investigated 100 mastectomized women in Tabriz-Iran, 2018. The participants were selected using the convenience sampling method. Data was collected using a sociodemographic questionnaire, the Health Promoting Lifestyle Profile II (HPLP-II), and the General Self-Efficacy Scale by Sherer. The multivariate general linear model with adjusting the sociodemographic variables was used to determine the relationship of the health-promoting lifestyle with self-efficacy. RESULTS: The mean±SD total score of the health-promoting behaviors was 135.5±16.7 from the obtainable score of 52 to 208. The highest and lowest mean scores were observed in the spiritual growth (25.4±4.3) and physical activity (15.2±4.4), respectively. The mean±SD self-efficacy score in this study was 57.3±7.4 from the obtainable score of 17 to 85. There was a significant positive correlation between the total score of the health-promoting lifestyle (r= 0.369; p<0.001) with self-efficacy. Results from the adjusted general linear model showed that the age, educational attainment of the spouse, and self-efficacy were the health-promoting lifestyle predictors. CONCLUSION: The findings of this study indicate the importance of self-efficacy and modifiable variables such as education in the engagement of mastectomized women in the health-promoting lifestyle. Regarding the positive relationship of self-efficacy with the health-promoting lifestyle, it seems that the interventional attempts to improve self-efficacy in these patients especially with considering the variables of age and spouse’s educational level can contribute to the improvement of the health-promoting lifestyle.